Barriers and Solutions to Passing State Legislation to Protect the Rights of Parents With Disabilities: Lessons From Interviews With Advocates, Attorneys, and Legislators. (June 2022) - Albert, Sasha M.; Powell, Robyn M.; Rubinstein, Jack
Parents with disabilities experience discrimination within the child welfare, family law, and adoption and foster care systems. In response, there have been increasing calls for states to pass legislation prohibiting discrimination against parents with disabilities, and as of 2020, 28 states have passed or are considering such legislation. This qualitative study explored the perspectives of 19 advocates, attorneys, and legislators on barriers and solutions for passing legislation to protect the rights of parents with disabilities. Participants identified three barriers: (a) legislators' pejorative attitudes toward parents with disabilities, (b) external opposition, and (c) legislative barriers. Participants also identified eight solutions: (a) cross-disability advocacy, (b) education, (c) relationship-building, (d) bipartisanship, (e) support from state and national organizations, (f) strong sponsors, (g) incrementalism, and (h) model legislation. Study findings should help to inform ongoing legislative advocacy to protect the rights of parents with disabilities.